The Language Style Used by YouTuber Bailey Sarian in Chris Watts – 2000 Page Discovery Murder, Mystery & Makeup - Putri Wulandari Nurul Azmi; Shalehoddin; Adam; Juwita Boneka Sinaga (Universitas Islam Negeri Palopo, 2025)
This research analyzed the language style used by YouTuber Bailey Sarian in the video “Chris Watts – 2000 Page Discovery Murder, Mystery & Makeup” using Martin Joos's (1967) language style theory, which classified language styles into five types: frozen, formal, consultative, casual, and intimate. The purpose of this research is to determine what language style Bailey used in that video and which language style is dominant. Using descriptive qualitative methods, the document data collection technique, Miles and Huberman’s model analysis technique, and analytical template, the researcher identified and analyzed the video transcript, resulting in a total of 253 data, consisting of 5 formal styles, 113 consultative styles, 133 casual styles, and 2 intimate styles. The results show that Bailey Sarian uses informal and flexible language, making the storytelling more engaging, easy to understand, and emotionally resonant, while still maintaining its informative purpose. No frozen language styles were found in the analyzed data. It can be seen that the dominant language style used was casual. This research concluded that the appropriate language style served an important role in the effectiveness of storytelling content on social media such as YouTube.